2022
DOI: 10.3390/nu14061133
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal FZD-7 Expression Is Modulated by Different Lifestyle Interventions in Patients with NAFLD

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a multifactorial condition characterized from hypertriglyceridemia and hepatic fat accumulation, in the absence of alcohol intake. NAFLD starts as steatosis (NAFL), and the continued injury relative to the toxic fat induces inflammation, steatohepatitis (NASH), and HCC. One of the factors determining liver degeneration during the evolution of NAFLD is a modification of Wnt/Frizzled (FZD) signaling. In particular, an inhibition of Wnt signaling and an overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Ma L et.al reported that MSC-derived exosomes loaded with therapeutic circRNAs-circDIDO1 suppressed HSC activation in liver fibrosis [ 49 ]. In another study, researchers utilized plasma-derived exosomes containing FZD receptor protein (FZD7) to modulate the dysregulated Wnt/Frizzled (FZD) signaling in nonalcoholic fatty liver disease (NAFLD) [ 50 ]. These studies unveiled that different kinds of exosomes are natural nanoparticles for rescuing liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Ma L et.al reported that MSC-derived exosomes loaded with therapeutic circRNAs-circDIDO1 suppressed HSC activation in liver fibrosis [ 49 ]. In another study, researchers utilized plasma-derived exosomes containing FZD receptor protein (FZD7) to modulate the dysregulated Wnt/Frizzled (FZD) signaling in nonalcoholic fatty liver disease (NAFLD) [ 50 ]. These studies unveiled that different kinds of exosomes are natural nanoparticles for rescuing liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Medium derived from both HGC27-R and KATOIII-R was processed for exosome isolation, in according to a previously published procedure ( 27 ) and as reported in the MISEV 2018 guidelines ( 28 ). Briefly, the culture medium of cells was centrifuged for 10 minutes at 1500× g (Thermo Scientific, Heraeus Multifuge X3 Centrifuge).…”
Section: Methodsmentioning
confidence: 99%
“…The pellet consisting of purified exosomes was recovered and dispersed in 200 μL of ultrapure water for the chemical-physical characterization and protein extraction or in sterile PBS for the cultured cell. After the exosome extraction, a characterization of freshly isolated exosome samples was performed by Dynamic Light Scattering (DLS) analysis, ς-Potential measurements and Transmission Electron Microscopy (TEM) investigation as previously reported ( 27 ). The remaining sample was stored at -80°C until protein extraction was assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, microarray analysis of exosomal miRNAs isolated from the serum of 41 patients with NAFLD (diagnosed using liver biopsy) suggested that serum exosomal miRNAs could be used to assess the severity of NAFLD and identify potential targets for NAFLD treatment[ 33 ]. One of the determinants of liver degeneration in the progression of NAFLD is Wnt/frizzled (FZD) signalling; for example, FZD7 delivered by plasma-derived exosomes is a good candidate for a novel and effective biomarker for the diagnosis and prognosis of NAFLD[ 51 ].…”
Section: Engineered Exosomes Involved In the Diagnosis Of Nafldmentioning
confidence: 99%